THE INFLUENCE OF INFERENCING STRATEGY TOWARD STUDENTS’ READING ABILITY IN JUNIOR HIGH SCHOOL - Nuriski, Novita (JETA (Journal of English Teaching and Applied Linguistic), 2020)
Inferencing strategy is an activity to help the students focus on their understand of what they read. Students often become dependent on dictionaries for looking up new words as they read. This strategy used alone, can slow them down and lead them to incorrect definitions. Often, the information that students need is available if they look at other parts of the task and at their own resources. Guessing the meaning of unfamiliar words can help them quickly solve problems without their having to go to other people or reference material. Students can use resources to verify their guesses. The objectives of the research were to identify: (1) whether Inferencing Strategy is more effective than conventional technique to teach reading; and (2) whether average score of students’ reading ability which is taugh through Inferencing Strategy higher than which is taugh through conventional technique. The research method used in this research was experimetal method. The population of this research was the eleventh grade students of SMAN 7 Bandar Lampung, Lampung. The sample of research was XI Science 6 consisted 36 students and XI Science 7 consisted 34 students. The students in XI Science 6 were as experimental class who were taught using inferencing strategy and the students in XI Science 7 were as control class who were taught using conventional technique. The data were in the form quantitative data and they were taken from a test. They were the scores of students’ reading test after having eight times treatments for each class. The researcher analyzed the data using ttest formula. Based on the result of data analysis, the research findings are: (1) Inferencing strategy is an effective which can be used by the teacher to improve students’ reading ability; and (2) average score of students’ reading ability in experimental class was higher than in control class.